Clinicopathologic profiling and oncologic outcomes of secretory carcinoma of the breast - Piguo Gong (Nature Portfolio, 2021)
Abstract Secretory carcinoma of the breast (SCB) is a rather rare entity of invasive breast cancer, the clinicopathologic characteristics and survival outcomes remain to be elaborated. A retrospective review was conducted in SEER database. A total of 190 SCB patients identified in SEER were eligible for inclusion in the analysis. Median age at diagnosis was 56 years (range 2–96 years). Both sexes and bilateral breast could be affected. Intriguingly, the incidence of SCB tended towards to decreasing in recent decades. Small tumor burden was observed with a mean tumor size of 2.13 cm. In a subgroup with sufficient details, positive staining of estrogen receptor (ER) and progesterone receptor (PR) was 58% and 40%, respectively. The vast majority of patients were of well to moderate differentiation (86.86%) and negative regional lymph nodes involvement (70.71%). Nearly half of the patients took radiotherapy and chemotherapy. Seniors were inclined to have an inferior breast cancer specific survival (BCSS) than their younger counterparts (P = 0.018). Patients underwent breast conserving surgery (BCS) and radiotherapy had much better BCSS than its mastectomy counterparts (P = 0.014). Collectively, SCB is a clinical indolent invasive breast cancer with excellent prognosis. BCS in conjunction with radiotherapy would be a rational alternative for this distinct entity.